The role of rotational hand movements and general motor ability in children’s mental rotation performance - Jansen, Petra; Kellner, Jan (Frontiers in Psychology, 2015)
Mental rotation of visual images of body parts and abstract shapes can be influenced by simultaneous motor activity. Children in particular seem to have a strong coupling between motor and cognitive processes. We investigated the influence of a rotational hand movement performed by rotating a knob on mental rotation performance in primary school-age children (N= 83; Age range: 7.0-8.3 and 9.0-10.11 years). In addition, we assessed the role of motor ability in this relationship. Boys in the 7-8-year-old group were faster when mentally and manually rotating in the same direction than in the opposite direction. For girls and older children this effect was not found. A positive relationship was found between motor ability and accuracy on the mental rotation task: stronger motor ability related to improved mental rotation performance. In both age groups, children with more advanced motor abilities were more likely to adopt motor processes to solve mental rotation tasks if the mental rotation task was primed by a motor task. Our evidence supports the idea that an overlap between motor and visual cognitive processes in children is influenced by motor ability.